Foundations in Microbiology - Talaro, Kathleen P Talaro, Arthur (W.C. Brown, 1993)
This text is written using an all-encompassing taxonomical classification approach. By classifying each group of organisms and then discussing those which are pathogenic in greater detail, students have a better idea of how each microbe can affect the many different organ systems.